Arabic Competition Role for Self-Maturity Development Among the Students of Arabic Education Department - Yasmin, Latifa; Naim Madjid , Muh. (Jurnal Locus Penelitian dan Pengabdian, 2026)
Arabic language competitions are not only platforms for linguistic achievement but also play a strategic role in fostering students’ self-maturity. This study aims to examine the role of Arabic competitions in developing self-maturity and Arabic language competence among students of the Arabic Education Department. This research employed a descriptive qualitative method involving 16 students who had participated in Arabic competitions. Data were collected through questionnaires analyzed using the Respondent Achievement Level technique and supported by in-depth interviews. The findings indicate that participation in Arabic competitions positively contributes to the development of self-maturity, particularly in self-confidence, emotional control, discipline, and responsibility. In addition, students’ Arabic language competencies—listening, speaking, reading, and writing—also showed improvement, with overall results categorized as good. The study concludes that Arabic competitions function as an effective catalyst for enhancing both self-maturity and Arabic language competence, and thus are relevant to be integrated into academic and extracurricular programs.